Training modalities and self-medication behaviors in a sample of runners during an ultratrail - André, C.; Girard, J.; Gautier, S.; Derambure, P.; Rochoy, M. (Science & Sports, 2020)
Aims: Training modalities, health and self-medication behaviors of athletes with high training level are not well-known. Our goal was to study these specifications during an ultramarathon race of 65km with 3500 meters of positive altitude difference ("6000D") and determine factors associated with better performance. Methods: We conducted a transversal and descriptive survey by questionnaire. Three hundred questionnaires were distributed (random sampling) and explained by the principal investigator during the 2 days before the 2016 edition of La 6000D. Results: One hundred and ninety two men and 20 women replied (mean age: 40.8±10.3 years and BMI: 22.6±2.1kg/m2). Runners averaged 7±6.1 years of practice. They trained specifically 12.1±10.4 weeks, traveled 64.5±30km per week in 7.6±5.1hours, with an average altitude difference of 1205±1172 meters. Half of the runners used food supplements before the race. Seventy-two runners (34%) had taken or planned to take drugs in the race: half of them were NSAIDs and 65.6% were not at risk of using NSAIDs. Main factors statistically associated with an improved performance were weekly training volume in the 2 months preceding the race, BMI, best marathon time, body fat percentage, weekly altitude gain, age, affiliation at a club, use of gels during the race, weekly kilometric volume, sex, use of spirulina and years of practice. Conclusion: We evidence some factors that seem to be associated with an improved performance: low age, low BMI, high years of practice, high weekly hours and club membership. Contrary to popular belief among runners, performance seems not or only slightly improved by intake or medication before, during or after the race (sports cake, multi-vitamin complex, BCAA, paracetamol, NSAID, beta-2-mimetics, etc.). Some of these relationships may exist and may not be clearly perceived by athletes. However, such results can help practitioners communicate with more confidence about the risks of certain supplements and NSAIDs compared to a non-significant performance advantage.